Give a Man a Fish or Teach a Man to Fish: A Cross-Level Moderated Mediation Model of Cognitive and Performance Responses of Team Members to Help of Team Leaders - Zhu, Yanting; Zhang, Lihua; Guo, Yungui (Frontiers in Psychology, 2021)
Drawing upon the theoretical lenses of social cognitive theory, this study explores whether, when, why, and how team leaders’ helping behavior influence team members’ individual work role performance (in terms of individual task proficiency, task adaptivity, and task proactivity) through team members’ self-efficacy. The consequences of different types of leaders’ help are unpacked in this study. By proposing a cross-level moderated mediation model and using multisource and multistage data from 303 team members in 39 work teams, leaders’ autonomy-oriented help was found to have a differential effect on team members’ individual work role performance via the latter’s self-efficacy when controlling for leaders’ dependency-oriented help. Moreover, the multilevel analysis of moderation uncovered that leader-member exchange relationship at the team level engendered a boundary condition for the mediating role of team members’ self-efficacy in the relationship between leaders’ autonomy-oriented help and member’s individual work role performance in this model.